2021
DOI: 10.1016/j.ijid.2020.11.161
|View full text |Cite
|
Sign up to set email alerts
|

A case of extremely prolonged viral shedding: Could cell cultures be a diagnostic tool to drive COVID-19 patient discharge?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…According to the kit specifications and our analysis, the analytical sensitivity of the Liferiver RT-PCR, used in our study, is 10 3 copies/mL using the QIAmp RNA extraction method; which aligns with the values obtained for the majority of amplification methods [ 15 , 16 , 30 , 31 ]. Long-term shedders of SARS-CoV-2 could experience higher and lower viral loads depending on the day of collection, but the general trend is that higher viral loads are required for isolation, although infectivity cannot be totally ruled out based on Vero cells’ infection only [ 32 , 33 ]. From our experience and from a meta-analysis, the chances of culturing SARS-CoV-2 from swabs when the RT-PCR Ct value of the specimen is >25 is very low (unpublished observations) [34] .…”
Section: Discussionmentioning
confidence: 99%
“…According to the kit specifications and our analysis, the analytical sensitivity of the Liferiver RT-PCR, used in our study, is 10 3 copies/mL using the QIAmp RNA extraction method; which aligns with the values obtained for the majority of amplification methods [ 15 , 16 , 30 , 31 ]. Long-term shedders of SARS-CoV-2 could experience higher and lower viral loads depending on the day of collection, but the general trend is that higher viral loads are required for isolation, although infectivity cannot be totally ruled out based on Vero cells’ infection only [ 32 , 33 ]. From our experience and from a meta-analysis, the chances of culturing SARS-CoV-2 from swabs when the RT-PCR Ct value of the specimen is >25 is very low (unpublished observations) [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high sensitivity of the qPCR assays, a very low number of virus genes can be detected, and SARS-CoV-2 RNA can be present in different body fluids for prolonged periods of time [7] . However, presence of virus genes does not translate into infectivity of the person, and studies have shown RNA positive samples to be negative for infectivity, particularly after longer time of shedding [ 8 , 9 ]. A previous study further observed that no respiratory samples with a SARS-CoV-2 qPCR Ct-value >24 showed infectivity in cell-culture [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is usually self-limiting. However, several evidences suggest the possibility of prolonged viral shedding and re-infection, giving rise to doubt on transmission potential and immunity protection [ 1 , 2 ]. Here we report the case of SARS-CoV-2 evolution and re-emergence three months after recovery presenting prolonged absence of humoral response and high production of virus-induced IFN-γ.…”
Section: Lettermentioning
confidence: 99%